A Comprehensive Approach to the Management of Patients With HLHS and Related Malformations: An Analysis of 83 Patients (2015-2021). Issue 5 (September 2022) - Bleiweis, Mark S.; Peek, Giles J.; Philip, Joseph; Fudge, James C.; Sullivan, Kevin J.; Co-Vu, Jennifer; DeGroff, Curt; Vyas, Himesh V.; Gupta, Dipankar; Shih, Renata; Pietra, Biagio "Bill" A.; Fricker, Frederick Jay; et al.
Background: Some patients with hypoplastic left heart syndrome (HLHS) and HLHS-related malformations with ductal-dependent systemic circulation are extremely high-risk for Norwood palliation. We report our comprehensive approach to the management of these patients designed to maximize survival and optimize the utilization of donor hearts.Methods: We reviewed our entire current single center experience with 83 neonates and infants with HLHS and HLHS-related malformations (2015-2021). Standard-risk patients (n = 62) underwent initial Norwood (Stage 1) palliation. High-risk patients with risk factors other than major cardiac risk factors (n = 9) underwent initial Hybrid Stage 1 palliation, consisting of application of bilateral pulmonary bands, stent placement in the patent arterial duct, and atrial septectomy if needed. High-risk patients with major cardiac risk factors (n = 9) were bridged to transplantation with initial combined Hybrid Stage 1 palliation and pulsatile ventricular assist device (VAD) insertion (HYBRID + VAD). Three patients were bridged to transplantation with prostaglandin.Results: Overall survival at 1 year = 90.4% (75/83). Operative Mortality for standard-risk patients undergoing initial Norwood (Stage 1) Operation was 2/62 (3.2%). Of 60 survivors: 57 underwent Glenn, 2 underwent biventricular repair, and 1 underwent cardiac transplantation. Operative Mortality for high-risk patients with risk factors other than major cardiac risk factors undergoing initial Hybrid Stage 1 palliation without VAD was 0/9: 4 underwent transplantation, 1 awaits transplantation, 3 underwent Comprehensive Stage 2 (with 1 death), and 1 underwent biventricular repair. Of 9 HYBRID + VAD patients, 6 (67%) underwent successful cardiac transplantation and are alive today and 3 (33%) died while awaiting transplantation on VAD. Median length of VAD support was 134 days (mean = 134, range = 56-226).Conclusion: A comprehensive approach to the management of patients with HLHS or HLHS-related malformations is associated with Operative Mortality after Norwood of 2/62 = 3.2% and a one-year survival of 75/83 = 90.4%. A subset of 9/83 patients (11%) were stabilized with HYBRID + VAD while awaiting transplantation. VAD facilitates survival on the waiting list during prolonged wait times.